Hubungan Antara Motivasi Intrinsik dan Kelincahan terhadap Kemampuan Menggiring Bola Pemain Massenrempulu Football Club - Saharullah Saharullah; Suci Ramadani Amaliah; Sulaeman Sulaeman; Nur Abidah Idrus (Departement of Mathematics Education, 2024)
The formulation of the problem in this research is whether there is a relationship between intrinsic motivation and agility on the ball dribbling ability of Massenrempulu Football Club players, while the aim of this research is to determine the relationship between intrinsic motivation and agility on the ball dribbling ability of Massenrempulu Football Club players. The research method used in this research is correlational research. By using analysis of measurement results. The population in this study were all Massenrempulu Football Club football players. With a total of 20 people using total sampling technique. Data collection techniques through questionnaire tests, agility tests and ball dribbling. Meanwhile, data analysis used SPSS version 20 using descriptive tests, normality tests and hypothesis tests. Based on the results of the data on the relationship between Intrinsic Motivation and Agility on the Ball Dribbling Ability of Massenrempulu Football Club Players, the results of the correlation analysis obtained data on the relationship between Intrinsic Motivation and Agility and Ball Dribbling Ability, a correlation coefficient of 0.173a with a significance of 0.003 was obtained. Ha was accepted because the significance was >0.05. So there is a significant relationship between Intrinsic Motivation and Agility and Ball Dribbling Ability involving 20 samples.